Protection of Women in Aceh Qanun No. 6 of 2014 concerning Jinayah Law (Acehnese Perception Analysis) - Soraya Devy; Fakhrurrazi M. Yunus (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2022)
The presence of Qanun jinayah is a blessing for Acehnese women. Therefore, it is the hope of all parties that the qanun can provide adequate protection for women. Several articles in Qanun no.6 of 2014 which regulate rape substantially encourage legal protection for women, including; with the stipulation that a person who deliberately commits rape is threatened with 'Uqubat Ta'zir flogging at least 125 (one hundred twenty five) times, a maximum of 175 (one hundred seventy five) times or a fine of at least 1,250 (one thousand two hundred and five) twenty) grams of pure gold, a maximum of 1,750 (one thousand seven hundred and fifty) grams of pure gold or imprisonment for a minimum of 125 (one hundred twenty five) months, a maximum of 175 (one hundred seventy five) months. Even if the rape is committed against children, the punishment is even more severe, namely being threatened with 'Uqubat Ta'zir flogging at least 150 (one hundred and fifty) times, a maximum of 200 (two hundred) times or a fine of at least 1,500 (one thousand five hundred) ) grams of pure gold, a maximum of 2,000 (two thousand) grams of pure gold or imprisonment for a minimum of 150 (one hundred and fifty) months, and a maximum of 200 (two hundred) months. Departing from the background of the problems above, this research is more focused on how the forms of women's protection in Qanun Aceh No. 6 of 2014 concerning Jinayah Law and what is the public's perception of the protection of women in the Qanun? The results of this study concluded that the existence of this qanun jinayah has not provided adequate protection for women. One of the reasons is the lack of socialization of the qanun jinayah and the lack of firmness by law enforcers in taking action against perpetrators. So that the perpetrators of harassment and rape are not afraid of the uqubat threat that has been stipulated for the perpetrators of criminal acts of harassment against women in the qanun jinayah.Kehadiran Qanun jinayah adalah sebuah berkah bagi kaum perempuan Aceh. Oleh karenanya menjadi harapan semua pihak bahwa qanun tersebut dapat memberikan perlindungan yang memadai kepada kaum perempuan. Beberapa pasal dalam Qanun no.6 tahun 2014 yang mengatur tentang pemerkosaan secara substansi sangat mendorong perlindungan hukum terhadap perempuan diantaranya; dengan penetapan bahwa bagi orang yang dengan sengaja melakukan Jarimah Pemerkosaan diancam dengan „Uqubat Ta‟zir cambuk paling sedikit 125 (seratus dua puluh lima) kali, paling banyak 175 (seratus tujuh puluh lima) kali atau denda paling sedikit 1.250 (seribu dua ratus lima puluh) gram emas murni, paling banyak 1.750 (seribu tujuh ratus lima puluh) gram emas murni atau penjara paling singkat 125 (seratus dua puluh lima) bulan, paling lama 175 (seratus tujuh puluh lima) bulan. Bahkan jika pemerkosaan dilakukan terhadap anak-anak maka hukumannya lebih berat lagi, yaitu diancam dengan „Uqubat Ta‟zir cambuk paling sedikit 150 (seratus lima puluh) kali, paling banyak 200 (dua ratus) kali atau denda paling sedikit 1.500 (seribu lima ratus) gram emas murni, paling banyak 2.000 (dua ribu) gram emas murni atau penjara paling singkat 150 (seratus lima puluh) bulan, paling lama 200 (dua ratus) bulan. Berangkat dari latar belakang permasalahan di atas maka penelitian ini lebih difokuskan pada bagaimana bentuk-bentuk perlindungan perempuan dalam Qanun Aceh No. 6 Tahun 2014 tentang Hukum Jinayah serta Bagaimana persepsi masyarakat tentang perlindungan perempuan dalam Qanun tersebut?. Hasil dari penelitian ini menyimpulkan bahwa kehadiran qanun jinayah ini belum memberikan efek perlindungan yang memadai kepada perempuan. Salah satu sebabnya adalah kurangnya sosialisasi terhadap qanun jinayah tersebut dan kurang tegasnya penegak hukum dalam menindak pelaku. Sehingga para pelaku pelecehan dan perkosaan tidak merasa takut dengan ancaman uqubat yang telah ditetapkan bagi pelaku tindak pidana pelecehan terhadap perempuan di dalam qanun jinayah tersebut.